Avaliação do potencial citotóxico, antifúngico e antibacteriano do extrato etanólico das folhas de Croton conduplicatus Kunth, em modelos experimentais in vitro - Pereira, Wandresa Francelino (2019)
Croton conduplicatus Kunth presents in its chemical composition major constituents terpenes, such as α- and β-pinenes, flavonoids, in addition to camphor, all those isolated from its extract, in which they present studies that stand out for the antibacterial, antifungal and antitumor activities. The present study aims to evaluate the activities: antifungal, cytotoxic, antibacterial and modulator of the ethanolic extract obtained from the leaves of Croton conduplicatus Kunth. For the evaluation of the antibacterial and antifungal activity the microdilution in broth methodology was carried out. To evaluate the cytotoxicity, the MTT (tetrazolium salt) methodology was used, using cells from the PC3 (Prostate), SNB-19 (Astrocytoma), HCT-116 (Colon) and HL60 (Leukemia) tumor cells. The ethanolic extract of the leaves of Croton conduplicatus Kunth has antimicrobial activity against strains of Escherichia coli, Klebsiella pneumoniae and Staphylococcus aureus, with minimum inhibitory concentrations (MIC), respectively: 64, 256 and 128 μg / mL; with respect to modulation in all strains and antibiotics, antagonism was detected, with MIC ≥1024 μg / mL. Regarding the antifungal activity, it was observed that the extract had activity against the Candida albicans strain (ATCC 40006) with a MIC of 128 μg / mL, but did not present the same result before the Candida tropicalis strain (ATCC 40042) with a MIC ≥1024 μg / mL, in relation to the modulation, antagonism was observed in relation to the physical interaction with neomycin. It can be observed that Croton conduplicatus was considered cytotoxic to the leukemic line (HL60), presenting IC 50 8.18 μg / mL. The other samples presented IC 50 higher than 100 μg / mL, which was the highest test concentration. In view of all the biological activities tested, it is necessary and extremely important to the continuity of in vitro tests followed by in vivo tests, so that the biological property required can be investigated more effectively, and thus contributing to the research and production of effective medicines.